Hollywood reborn : movie stars of the 1970s - Morrison, James, 1960- (Star decades: American culture/American cinema., 2010)
As studio and star systems declined in the 1970s, actors had more power than ever, and because many had become fiercely politicized by the temper of the times, the movies they made were often more challenging than before. Thus, just when it might have faded out, Hollywood was reborn-but what was the nature of this rebirth? Hollywood Reborn examines this question, offering new perspectives through the lens of important stars, and illuminating in the process some of the most fascinating and provocative films of the decade.